The mystery of the missing tooth - Hooks, William H.; Poydar, Nancy (Milwaukee, Wis. : Gareth Stevens Pub., 1998)
When Kara finally loses a tooth and can$1 (Bt find it anywhere, she wonders if the Tooth Fairy will still come, if she will bring a gift, and what she does with all those teeth.s
"A Byron Preiss book"
"Level 1 (Preschool-grade 1)"--cover.
Keywords: Tooth fairy -- Fiction; Lost and found possessions -- Fiction; Teeth -- Fiction